EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN SELF-EFFICACY SISWA SMP/MTS - Suparni Suparni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to determine whether learning using the PMRI approach is more effective than conventional learning on students ' problem-solving abilities and whether learning using the PMRI approach is more effective than conventional learning on students' self-efficacy. This study is a quasi-experimental study with a nonequivalent control group design. The independent variable is the PMRI approach, and the dependent variable is the students' problem-solving ability and self-efficacy. The population was class VIII student of SMP Negeri 15 Yogyakarta in 2018/2019, and samples of classes VIII D, VIII F and VIII I. The instrument was a matter of pretest-posttest problem-solving abilities and prescale-post scale self-efficacy, RPP , and LKS. Data analysis techniques used the t-test with the help of SPSS 16.0 software. The results are that learning using the PMRI approach is more effective than conventional learning on students ' problem-solving abilities, and learning using the PMRI approach is no more effective than conventional learning on students' self-efficacy.